Internalisasi Nilai Siddiq dan Amanah dalam Inovasi Pendidikan Islam Era Digital: Analisis Semangat Teacherpreneurship Nabi Muhammad SAW - Marzuki, Marzuki; Aprido, Mohamad; Muzaki, Ahmad; Samlawi, Samlawi; Kurniati, Edy Dwi (Indo-MathEdu Intellectuals Journal, 2026)
This article aims to examine the importance of internalising the values of Siddiq (honesty) and Amanah (responsibility) as the foundation for innovation in Islamic education in the digital age, particularly in shaping the character of students. The method used is a conceptual approach through literature analysis of Islamic education studies, prophetic character, and the concept of teacherpreneurship of the Prophet Muhammad SAW as a role model for modern teachers. The results of the study show that the value of Siddiq serves as the foundation of academic integrity in the digital learning process, while the value of Amanah serves as an ethical guideline in the professional responsibility of teachers towards the use of technology. The integration of these two values confirms that Islamic educational innovation rooted in prophetic spirituality is able to balance technological progress with the cultivation of noble character in students.